Solve for a a/3=(a-1)/2

Math
a3=a-12
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
a⋅2=3⋅(a-1)
Solve the equation for a.
Tap for more steps…
Move 2 to the left of a.
2a=3⋅(a-1)
Simplify 3⋅(a-1).
Tap for more steps…
Apply the distributive property.
2a=3a+3⋅-1
Multiply 3 by -1.
2a=3a-3
2a=3a-3
Move all terms containing a to the left side of the equation.
Tap for more steps…
Subtract 3a from both sides of the equation.
2a-3a=-3
Subtract 3a from 2a.
-a=-3
-a=-3
Multiply each term in -a=-3 by -1
Tap for more steps…
Multiply each term in -a=-3 by -1.
(-a)⋅-1=(-3)⋅-1
Multiply (-a)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1a=(-3)⋅-1
Multiply a by 1.
a=(-3)⋅-1
a=(-3)⋅-1
Multiply -3 by -1.
a=3
a=3
a=3
Solve for a a/3=(a-1)/2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top